Synthesis of a new class of iminosugars based on constrained azaspirocyclic scaffolds by way of catalytic C–H amination1. Issue 35 (21st September 2015) - Nocquet, Pierre-Antoine; Hensienne, Raphaël; Wencel-Delord, Joanna; Wimmer, Eric; Hazelard, Damien; Compain, Philippe
<x xml:space="preserve">Abstract</x> High level of regiocontrol has been achieved in the C–H amination of substrates with a high density of reactive C–H bonds, allowing the access to a new class of conformationally constrained iminosugars.